The Place of the Local Government in Nigeria’s Federal Arrangement - Abubakar Oladeji (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2022)
Multi-level government arrangements-federal, state/provincial and local government-are common to all federal systems. However, the place and role of local government in those systems vary markedly. In some, local government is a constitutionally recognised sphere of government, while in others it is merely a competence of the state/provincial government, or an administrative unit of a higher order of government. In some federal systems where it is recognised, like Nigeria, the local governments are principally established for socio-economic and political development at the grassroots. Thus, local governance is the prerogative of the local governments in Nigeria. This tier of government established by Section 7 of the 1999 constitution of the Federal Republic of Nigeria (as amended) has some of its functions detailed in the fourth schedule of the same constitution. The overall objective of this paper is the analysis of the current status of the local government within the Nigerian federal system, and a critical examination of what the future holds for the third tier of government in Nigeria. Using essentially secondary documentary method, with content and thematic analysis, the paper recommends incremental constitutional review (as against mega constitutional renewal), the need to enhance political and economic autonomy of local government through frequent elections, and adopting new strategies for generating internal revenues for the local government in Nigeria.